Суб’єкти відносин, пов’язаних з персональними даними - Теремецький, В. І.; Teremetskyi, V. I. (Право і безпека. - 2015. - № 2 (57). - С. 171–176., 2015)
Охарактеризовано суб’єктів відносин, пов’язаних з персональними даними, та визначено особливості їх правового статусу. Сформульовано авторське визначення суб’єкта персональних даних. Запропоновано поділяти суб’єктів відносин, пов’язаних із персональними даними, на основні, участь яких є обов’язковою, та факультативні. Обґрунтовано необхідність доповнення ст. 2 закону України «Про захист персональних даних» терміном «неналежний володілець» та визначення його статусу.

Some problems of legal regulation of the subjects of relations related to personal data are considered. Characteristics of the subjects of the mentioned relations are realized and peculiarities of their legal status are determined. It is emphasized that consolidation of only individuals as subjects of personal data, is intended to guarantee everyone in the state, protection of his personal data. The objective of the article is implementation of the characteristics of the subjects of relations related to personal data, and determining the features of their legal status. The methodological basis of the paper is a set of general scientific and special legal methods of research. With the help of logical and semantic method and method of ascent from the abstract to the concrete the author has deepen the conceptual apparatus, namely the nature of the terms «personal data» and «improper performer». The system and structural method is used for the classification of the subjects of relations related to personal data. Methods of analysis and synthesis made it possible to determine the problems of legal regulation of subjects of these relations and to develop scientific recommendations on its improvement. The author’s definition of the subject of personal data is formulated. It is found out that the subject of personal data does not naturally have complete set of information about itself, instead gets the information throughout the whole life. This indicates on the evolution of personal data and its transformation in the society. The author has suggested to share the subjects of relations related to personal data, depending on the legal status and procedural value into basic, which participation is mandatory, and optional, which can not be involved in these legal relations, and in case such a participation their status is significantly limited. The necessity to amend the Art. 2 of the Law of Ukraine «On Personal Data Protection» with the term «undue holder» is grounded; and its status is determined.

Охарактеризованы субъекты отношений, связанных с персональными данными, и определены особенности их правового статуса. Сформулировано авторское определение субъекта персональных данных. Предложено разделять субъектов отношений, связанных с персональными данными, на основные, участие которых является обязательным, и факультативные. Обоснована необходимость дополнения ст. 2 закона Украины «О защите персональных данных» термином «ненадлежащий владелец» и определение его статуса.
Teremetskyi, V.I. (2015), “Subjects of relations related to personal data” [“Subiekty vidnosyn, poviazanykh z personalnymy danymy”], Pravo i Bezpeka, No. 2, pp. 171–176.
Теремецький, В. І. Суб’єкти відносин, пов’язаних з персональними даними // Право і безпека. - 2015. - № 2 (57). - С. 171–176.
Keywords: Цивільне право. Civil Law. Гражданское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; суб’єкти відносин, пов’язаних з персональними даними; персональні дані; захист персональних даних; неналежний володілець; subjects of relations related to personal data; personal data; protection of personal data; improper holder; субъекты отношений, связанных с персональными данными; персональные данные; защита персональных данных; ненадлежащий владелец